Carambola Growing in the Florida Home Landscape - Jonathan H. Crane (EDIS)
This document provides a comprehensive overview of carambola, also known as star fruit, detailing its cultivation, varieties, and environmental requirements. It highlights the tree's growth patterns, optimal conditions for fruit production, and the importance of proper planting and care. The article also addresses potential challenges such as pests, diseases, and environmental stressors, offering solutions for effective management. Additionally, it emphasizes the nutritional value and various uses of carambola, making it a valuable addition to home landscapes in suitable climates. Original publication date April 1994.